The Story of "The Sons of the prophets" and its Implications for the school of Theology Universitas Klabat Discipleship Training Program - sepang, douglas (12th International Scholars Conference 2025, 2026)
This paper aimed to review the roles of the Old Testament prophets, the sons of the prophets, and the implications of their roles to be applied to Universitas Klabat Theology discipleship training program. This literature review paper discussed three prophets of the Old Testament based on 1 Samuel 19:18-24, 2 Kings 2, and 2 Kings 4:38-44, which focus on Samuel, Elijah, and Elisha as the prophets. Google Scholar and Research Gate were utilized to find related literature. As for bible commentaries related to the three bible chapters, literature focuses on Ellen White’s writings were used in addition to other literature. The review results revealed that a discipleship training program needs to train students to preserve the value of the education they received to be passed on to their students and the next generation as well. The focus of the training is to educate students’ minds through knowledge of God and His law, physics through developing empathy and willingness to help others, and social needs to tend to those who are in need. These values must be preserved and taught throughout generations to produce future teachers who are grounded in the same values as those taught by Samuel, Elijah, and Elisha in their school of prophets.